Corporate Diversification and CEO Compensation: Evidence from the Moderating Effect of Firm Performance - Hwei Cheng Wang; Ya Ying Chou Yeh; Michael D. Slaubaugh; Chih Chi Fang (STIE Malangkucecwara, 2020)
This study explores whether firm performance moderates the relationshipbetween corporate diversification and CEO compensation. A sample of 2,448 CEOcompensations across 1,622 firms from 1997 to 2002 was used to test several hypotheses.Corporate diversification was divided into two categories (international and industry) andfirm performance was defined using both market-based and accounting-based measures.For the relationship between international diversification and CEO compensation, ourresults indicate that both market-based and accounting-based firm performance had asignificant negative effect on that relationship. Furthermore, accounting-based firmperformance was a better predictor of international diversification and CEOcompensation than market-based firm performance. For the relationship betweenindustry diversification and CEO compensation, however, our results show that onlymarket-based firm performance had a significant negative influence whereas accountingbased firm performance did not have any significant influence.